Power Relations and Patriarchal Ideology: The Agency of Madurese Women in Indonesian Novels through Critical Discourse Analysis - Ria Kasanova; Mohammad Rudiyanto (JURNALISTRENDI : JURNAL LINGUISTIK, SASTRA, DAN PENDIDIKAN, 2026)
This study examines the representation of Madurese women in contemporary Indonesian novels using a critical discourse analysis (CDA) approach. It focuses on how power relations and patriarchal ideologies are constructed and negotiated in Paraban Tuah, Damar Kambang, and Rumah Jeddah. This study aims to identify discursive strategies that naturalise women’s subordination while exploring the forms of agency embedded within the narrative structure. Employing Fairclough’s three-dimensional CDA model, this comparative analysis investigates the textual, discursive, and social dimensions of the novels. The findings reveal that patriarchy is naturalised through morally evaluative lexical choices, metaphors of honour, and deontic modalities that frame women’s obligations within the authority of custom and religion. At the narrative level, symbolic domination and the centralisation of male voices institutionalise power relations as the cultural norm. However, female characters are not portrayed as entirely passive; agency emerges through implicit resistance, domestic negotiation, and ambivalence between compliance and defiance in their lives. Theoretically, this study strengthens the application of critical discourse analysis in Indonesian literary studies and conceptualises agency as a discursive negotiation within ethnicity-based patriarchal structures